ELF3, ELF5, EHF and SPDEF Transcription Factors in Tissue Homeostasis and Cancer - Ian Y. Luk; Camilla M. Reehorst; John M. Mariadason (Molecules, 2018)
The epithelium-specific ETS (ESE) transcription factors (ELF3, ELF5, EHF and SPDEF) are defined by their highly conserved ETS DNA binding domain and predominant epithelial-specific expression profile. ESE transcription factors maintain normal cell homeostasis and differentiation of a number of epithelial tissues, and their genetic alteration and deregulated expression has been linked to the progression of several epithelial cancers. Herein we review the normal function of the ESE transcription factors, the mechanisms by which they are dysregulated in cancers, and the current evidence for their role in cancer progression. Finally, we discuss potential therapeutic strategies for targeting or reactivating these factors as a novel means of cancer treatment.